TINJAUAN YURIDIS KARTEL TIKET PESAWAT MASKAPAI DOMESTIK PENERBANGAN PT. GARUDA INDONESIA DENGAN LION GROUP - Ikromi, Eka Putri Fauzia; M.T.V.M., Sri Maharani (Fakultas Hukum Universitas Gresik, 2020)
ABSTRACT In order to create conducive stability and business competition in Indonesia, Law Number 5 Year 1999 concerning the prohibition of monopolistic practices and unfair business competition is the main condition to be considered in Indonesia. In its enforcement, the Government established the KPPU institution as a supervisor of the actions of business actors which are often violated to increase profits for personal interests, one of which is price conspiracy or so-called cartels. The majority who do this come from business people who control the Indonesian market economy. The aviation business sector in Indonesia is currently receiving the spotlight from KPPU for an indication of a flight ticket cartel which is the two major domestic airlines in Indonesia, namely PT. Garuda Indonesia and Lion Group. Even if there is no written agreement, the cartel can be charged to business actors who in practice carry out prohibited acts and can harm other airlines. The actions of the airline PT. Garuda Indonesia and Lion Group are reviewed legally based on existing business competition regulations in Indonesia and are examined according to the procedures set out in Perkom Number 1 of 2019. This review aims to assess the alleged flight ticket cartel by both domestic airlines, whether it has violated it or not.Keyword : KPPU, Cartel and Law Number 5 Year 1999Ãƒâ€šÃ‚Â ABSTRAKUntuk menciptakan stabilitas yang kondusif dan persaingan bisnis di Indonesia, Undang-Undang Nomor 5 Tahun 1999 tentang larangan praktik monopoli dan persaingan usaha tidak sehat adalah syarat utama yang harus dipertimbangkan di Indonesia. Dalam penegakannya, Pemerintah membentuk lembaga KPPU sebagai pengawas tindakan pelaku usaha yang kerap dilanggar untuk menambah keuntungan demi kepentingan pribadi, salah satunya adalah konspirasi harga atau yang disebut kartel. Mayoritas yang melakukan ini berasal dari pelaku bisnis yang mengendalikan ekonomi pasar Indonesia. Sektor bisnis penerbangan di Indonesia saat ini menerima sorotan dari KPPU untuk indikasi kartel tiket penerbangan yang merupakan dua maskapai domestik utama di Indonesia, yaitu PT. Garuda Indonesia dan Lion Group. Bahkan jika tidak ada perjanjian tertulis, kartel dapat dibebankan kepada pelaku bisnis yang dalam praktiknya melakukan tindakan yang dilarang dan dapat membahayakan maskapai lain. Tindakan maskapai PT. Garuda Indonesia dan Lion Group ditinjau secara legal berdasarkan peraturan persaingan bisnis yang ada di Indonesia dan diperiksa sesuai dengan prosedur yang ditetapkan dalam Perkom Nomor 1 tahun 2019. Tinjauan ini bertujuan untuk menilai dugaan kartel tiket penerbangan oleh kedua maskapai domestik, apakah memiliki melanggar atau tidak.Kata kunci: KPPU, Kartel, dan Undang-Undang Nomor 5 Tahun 1999